Investigation on the Effect of Impeller Design Parameters on Performance of a Low Specific Speed Centrifugal Pump Using Taguchi Optimization Method - Ayremlouzadeh, Hadi; Jafarmadar, Samad; Amini Niaki, Seyed Reza (International Journal of Fluid Power, 2022)
In order to investigate the effect of blade design on pump performance, a CFD analysis was carried out, and the results were compared with experimental performance data of a low specific speed radial pump, which presents a good agreement. After model verification, the effect of impeller geometrical parameters includes blade outlet angle, wrap angle, and width at the exit, was investigated on the pump’s performance. Moreover, these parameters were chosen on three levels using an L9 orthogonal standard array of the Taguchi optimization method. The efficient levels of variables were calculated using the analysis of variance (ANOVA) method. The results revealed that impeller width at exit and blade outlet angle is the most effective pump shaft power and efficiency parameters. To minimize power, the optimal levels are the outlet angle of 27<span id="MathJax-Element-1-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: 400; line-height: normal; font-size: medium; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: 0px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; color: #000000; font-family: 'Times New Roman'; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; position: relative;" tabindex="0" role="presentation" data-mathml="∘">∘∘, wrap angle of 150<span id="MathJax-Element-2-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: 400; line-height: normal; font-size: medium; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: 0px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; color: #000000; font-family: 'Times New Roman'; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; position: relative;" tabindex="0" role="presentation" data-mathml="∘">∘∘, and width at the exit of 9 mm. Further, an outlet angle of 23<span id="MathJax-Element-3-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: 400; line-height: normal; font-size: medium; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: 0px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; color: #000000; font-family: 'Times New Roman'; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; position: relative;" tabindex="0" role="presentation" data-mathml="∘">∘∘, a wrap angle of 155<span id="MathJax-Element-4-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: 400; line-height: normal; font-size: medium; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: 0px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; color: #000000; font-family: 'Times New Roman'; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; position: relative;" tabindex="0" role="presentation" data-mathml="∘">∘∘, and a width at the exit of 9 mm lead to maximum pump efficiency. According to the validation simulations, an increase of 2.4% inefficiency and a minimum power of 3.9KW were achieved. The Overall Evaluation Criteria (OEC) technique revealed that considering 23<span id="MathJax-Element-5-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: 400; line-height: normal; font-size: medium; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: 0px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; color: #000000; font-family: 'Times New Roman'; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; position: relative;" tabindex="0" role="presentation" data-mathml="∘">∘∘, 160<span id="MathJax-Element-6-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: 400; line-height: normal; font-size: medium; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: 0px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; color: #000000; font-family: 'Times New Roman'; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; position: relative;" tabindex="0" role="presentation" data-mathml="∘">∘∘, and 9 mm for outlet angle, wrap angle, and width at the exit, minimum shaft power, and maximum pump efficiency will be achieved. ANOVA introduced width at the exit as the most governing parameter of pump performance characteristics.